2008
DOI: 10.1007/s10517-008-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of picrotoxin on organism’s resistance to acute severe hypoxia

Abstract: Organism's resistance to acute severe hypoxia (3% O2) was studied after administration of GABA(A) receptor antagonist picrotoxin and adenosine receptor antagonist euphylline (aminophylline) and after neutralization of secondary hypocapnia by adding 7% CO2 to the hypoxic mixture. Administration of picrotoxin to anesthetized rats increased animal resistance to hypoxia. The resistance to hypoxia decreased after treatment with euphylline. Neutralization of secondary hypocapnia by adding 7% CO2 to the hypoxic mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Mean values of the resistance to hypoxia in the control pre-tested rat groups are shown in Figure 1. In our study, the rats with low, intermediate and high resistance to SHBH comprised 36%, 27% and 38%, respectively, of the tote pre-tested rats (n = 64), which corresponds to the usual composition of outbred rats in an experimental lot [28] [32]. (Figure 1(a) and Figure 1(b)).…”
Section: Resistance To Shbh Of the Intact High And Low Resistance Ramentioning
confidence: 74%
“…Mean values of the resistance to hypoxia in the control pre-tested rat groups are shown in Figure 1. In our study, the rats with low, intermediate and high resistance to SHBH comprised 36%, 27% and 38%, respectively, of the tote pre-tested rats (n = 64), which corresponds to the usual composition of outbred rats in an experimental lot [28] [32]. (Figure 1(a) and Figure 1(b)).…”
Section: Resistance To Shbh Of the Intact High And Low Resistance Ramentioning
confidence: 74%
“…A severe hypoxia (3% O 2 , rat) in the first few minutes, like in the moderate hypoxia, initiated the same dynamics in the increase of minute tidal volume and respiratory frequency [40][41][42], and picrotoxin (i.v.) significantly potentiated the activation of both respiratory functions (cat and rat) [42]. Also, the authors observed that these effects of picrotoxin were most pronounced in the high resistance rats compared with low and intermediate resistance rats.…”
Section: Gabaergic Systemmentioning
confidence: 73%
“…administration of GABA A receptor antagonist picrotoxin enhanced ventilation through an increase in respiratory frequency and minute tidal volume (rat) [42]. A severe hypoxia (3% O 2 , rat) in the first few minutes, like in the moderate hypoxia, initiated the same dynamics in the increase of minute tidal volume and respiratory frequency [40][41][42], and picrotoxin (i.v.) significantly potentiated the activation of both respiratory functions (cat and rat) [42].…”
Section: Gabaergic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…We used high-frequency ultrasonic Doppler system working at a frequency of 33 MHz for recording blood fl ow velocity in rat a. basilaris without opening the skull. We used an invasive methodology used for central injection through the occipital membrane into the cavity of the cerebral ventricle IV [6]. The aim of our experiment was to evaluate the effi ciency of this approach in studies of the hemodynamics in the cerebral basilar arteries.…”
mentioning
confidence: 99%